2012
DOI: 10.1890/11-0503.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tropical insect herbivore abundance from host plant traits and phylogeny

Abstract: Abstract. Phylogenetic ecology has identified patterns of diversity in communities that may find explanation in trophic interactions, and yet there have been few attempts to directly relate such patterns among trophic levels. Density-dependent processes involving pests and pathogens, for example, have been invoked to account for plant community phylogenetic patterns, but relatively little is known about how plant relatedness might affect community structure at other trophic levels. We examined the degree to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 87 publications
7
121
0
Order By: Relevance
“…Th e strength of host species interacting with herbivores can be infl uenced by density-dependent processes. Th e most abundant plant species (i.e., those with most biomass or cover) tend to be related to a greater number of herbivore species ( Basset, 1991 ;Marques et al, 2000 ;Whitfeld et al, 2012 ) simply by having a greater probability of being found, that is, a greater apparency ( Feeny, 1976 ). However, in the particular case of tropical systems, where herbivorous insects are highly specialized to their host plants ( Novotny et al, 2002 ;Novotny and Basset, 2005 ;Ødegaard et al, 2005 ;Weiblen et al, 2006 ;Forister et al, 2012Forister et al, , 2015, it is likely that species strength is independent from the host plants biomass or abundance.…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 99%
“…Th e strength of host species interacting with herbivores can be infl uenced by density-dependent processes. Th e most abundant plant species (i.e., those with most biomass or cover) tend to be related to a greater number of herbivore species ( Basset, 1991 ;Marques et al, 2000 ;Whitfeld et al, 2012 ) simply by having a greater probability of being found, that is, a greater apparency ( Feeny, 1976 ). However, in the particular case of tropical systems, where herbivorous insects are highly specialized to their host plants ( Novotny et al, 2002 ;Novotny and Basset, 2005 ;Ødegaard et al, 2005 ;Weiblen et al, 2006 ;Forister et al, 2012Forister et al, , 2015, it is likely that species strength is independent from the host plants biomass or abundance.…”
Section: Study Site -Fieldwork Was Done At the Centro De Investigacionesmentioning
confidence: 99%
“…Field methods were similar to our previous study at Wanang (Miller et al 2013, Whitfeld et al 2012. Ten 45 x 45 m (0.2025 ha) plots were surveyed for woody stems with a diameter at breast height (DBH) ³ 5 cm, along with woody epiphytes with stems ³ 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…This paper provides metadata for DNA barcodes (cytochrome coxidase I sequences, COI) in GenBank for a collection of specimens from ecological studies in Yawan, Morobe Province, Papua New Guinea (PNG), sampled as part of long term research on the ecology and taxonomy of herbivorous insects in PNG (Miller et al 2003, Whitfeld et al 2012). This paper aims to make DNA barcode data available to document ongoing research, to contribute to the International Barcode of Life (iBOL; www.ibol.org) project, and to encourage enhancement in species identification, in line with the concept of DNA barcode data release papers and the Fort Lauderdale principles for genetic data (Schindel et al 2011).…”
mentioning
confidence: 99%
“…The NGBRC established two one-ha research forest plots, one in primary forest and one in secondary forest, and all trees >5 cm DBH were identified, tagged and mapped. The NGBRC study involved the felling of all trees and lianas in the two plots [46]. D. Warakai carried out cavity census of all trees >5 cm DBH on these two forest plots, from 18 February 2006 to 3 March 2006, before the trees were felled.…”
Section: Tree Plot Cavity Censusmentioning
confidence: 99%